Reinventing Management : Smarter Choices for Getting Work Done. - Birkinshaw, Julian (John Wiley & Sons, 2010)
The recent economic crisis was not just caused by a failure of regulation or economic policy; it was a story of the failure of management in a fundamental sense--a deeply flawed approach to management that encouraged bankers to pursue opportunities without regard for their long-term consequences, and to put their own interests ahead of those of their employers and their shareholders. And looking more widely, there is a creeping disenchantment with management as a profession: surveys show that managers generate less respect than lawyers and bankers in the eyes of the general public, and there ar.